Efficacy of a deltamethrin-based pour-on in the control of tick-borne diseases and trypanosomosis in Kwale District, Kenya - Muraguri, G.R.; McLeod, A.; McDermott, John J. (Springer, 2003)
A one-year longitudinal study was conducted in 92 smallholder diary farms in Kwale district of Kenya, to evaluate the efficacy of Spot-on® (a 10% deltamethrin pour-on) in the control of East Coast fever, anaplasmosis, babesiosis and trypanosomosis. A comparison of the annual incidence and mortality rates from these diseases was made among four Spot-on® application regimes: biweekly, monthly, bimonthly and untreated control groups. The incidence of East Coast fever, ranging from 2.6 to 6.8% among the treated animals, was significantly lower than in the control group (18.8%). Anaplasmosis incidence ranged from 2.6 to 13.5%, but the differences among the treatments were not statistically significant. There were only seven confirmed cases of babesiosis and therefore no statistical comparisons of the incidence rates were made. The incidence rates of trypanosomosis in the biweekly- (28.2%) and monthly-treated animals (38.6%) were statistically lower than in the bimonthly (63.9%) and control groups (72.6%). It was concluded that monthly application of Spot-on® could significantly reduce the incidence of tick-borne diseases and trypanosomosis in cattle in the coastal lowlands.